1999
DOI: 10.1016/s0304-3959(98)00184-5
|View full text |Cite
|
Sign up to set email alerts
|

The cortical representation of pain

Abstract: Anatomical and physiological studies in animals, as well as functional imaging studies in humans have shown that multiple cortical areas are activated by painful stimuli. The view that pain is perceived only as a result of thalamic processing has, therefore, been abandoned, and has been replaced by the question of what functions can be assigned to individual cortical areas. The following cortical areas have been shown to be involved in the processing of painful stimuli: primary somatosensory cortex, secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
561
0
25

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 954 publications
(618 citation statements)
references
References 49 publications
32
561
0
25
Order By: Relevance
“…In addition to terminations in the major homeostatic regions of the brainstem, spinothalamic neurons project to nuclei in medial and ventral posterior lateral regions of the thalamus. An anatomical and functional distinction is made frequently between lateral and medial pain pathways that are constituted by the targets of projections from the respective groups of thalamic nuclei [Treede et al, 1999]. The classic termination of the spinothalamic pathway, the primary somatosensory cortex is synonymous with the lateral pain pathway and has been ascribed with sensory/discriminative functions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to terminations in the major homeostatic regions of the brainstem, spinothalamic neurons project to nuclei in medial and ventral posterior lateral regions of the thalamus. An anatomical and functional distinction is made frequently between lateral and medial pain pathways that are constituted by the targets of projections from the respective groups of thalamic nuclei [Treede et al, 1999]. The classic termination of the spinothalamic pathway, the primary somatosensory cortex is synonymous with the lateral pain pathway and has been ascribed with sensory/discriminative functions.…”
Section: Discussionmentioning
confidence: 99%
“…Kenshalo and Willis (1991) and Treede et al (1999) have recently reviewed the evidence for a role of the cerebral cortex in the perception and control of pain. The numerous PET studies have revealed activity in the human sensorimotor cortex during pain (for reviews, see Bushnell et al, 1999;Casey, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, most of these studies have relied on non-invasive functional neuroimaging techniques to sample, directly or indirectly the neural activity triggered by various kinds of nociceptive stimuli showing that nociceptive stimuli elicit responses in several subcortical and cortical brain structures [13][14][15][16][17][18][19][20][21]. The responses in some of these structures are observed consistently across studies, and seem to be correlated with the perceived intensity of pain.…”
Section: Afferent Pathwaysmentioning
confidence: 99%